2007
DOI: 10.1002/ceat.200700060
|View full text |Cite
|
Sign up to set email alerts
|

An Electrospray Method Using a Multi‐Capillary Nozzle Emitter

Abstract: A multi-capillary nozzle emitter consisting of one metal plate with capillary nozzles and a ring type counter electrode was used as a multi-electrospray atomizer. The number of capillary nozzles, flow rate of the liquid and the interval between the capillary nozzles were changed, and the droplet diameter and the voltage required for a steady cone-jet mode were measured. For the multi-capillary nozzle emitter, the interaction between the capillary nozzles is the important factor for obtaining fine droplets of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…26 For a sharpened-end 20-nozzle emitter, the optimal voltage was 3.5 kV, confirming the aforementioned internozzle interactions. 30 We observed that both the optimal voltage and MS sensitivity increased with nozzle numbers. For example, there was an on average ~2-fold increase in sensitivity for the 20-nozzle relative to the 1-nozzle emitters.…”
Section: High-throughput Mass Spectrometry Using Multinozzle Emitter mentioning
confidence: 66%
See 1 more Smart Citation
“…26 For a sharpened-end 20-nozzle emitter, the optimal voltage was 3.5 kV, confirming the aforementioned internozzle interactions. 30 We observed that both the optimal voltage and MS sensitivity increased with nozzle numbers. For example, there was an on average ~2-fold increase in sensitivity for the 20-nozzle relative to the 1-nozzle emitters.…”
Section: High-throughput Mass Spectrometry Using Multinozzle Emitter mentioning
confidence: 66%
“…3a). This was due to the linear format of the nozzle array, the position of the nozzle array relative to the ion cone (Z-spray), the nozzle-nozzle interactions (shielding effects), 30 and the interactions between the emitter stem and the nozzles on the two edges (i.e., the edge effects). Consistently, we observed even higher electric fields at the corner of the nozzles on two edges, i.e., 6.6×10 6 (left corner, not labeled) vs. 5.8×10 6 (center, labeled)…”
Section: Electric Fields On the Multinozzle Emitter Arraysmentioning
confidence: 99%
“…3a). This was due to the linear format of the nozzle array, the position of the nozzle array relative to the ion cone (Z-spray), the nozzle-nozzle interactions (shielding effects), 30 and the interactions between the emitter stem and the nozzles on the two edges (i.e., the edge effects). Consistently, we observed even higher electric fields at the corner of the nozzles on two edges, i.e., 6.6×10 6 (left corner, not labeled) vs. 5.8×10 6 (center, labeled) for the leftmost nozzle; and 6.1×10 6 (right corner, not labeled) vs. 5.7×10 6 (center, labeled) for the rightmost nozzle, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An important point which comes to mind at this point is that a spray diameter of 1.5 cm gives a spray area of just 1.76 cm 2 , which is small when viewed from the perspective of bulk manufacturing. The answer to this is multi-nozzle spray deposition [31,32] in which hundreds of nozzles are embedded in the system. The multi-nozzle setup also takes care of the dual spray region phenomenon as the mild regions of two adjacent nozzles will overlap (being at the periphery) and hence the concentration will double in the overlapping edge region thereby mitigating the drawback of dual spray region as well.…”
Section: Effect Of Standoff Distancementioning
confidence: 99%